Wirtualni idole na k-popowej scenie muzycznej - Łukomska, Maria (Zagadnienia Rodzajów Literackich, 2023)
Culture is constantly changing the model of the famous person. Over time, they have been going through different forms of fame. Now celebrities collide with the online culture. However, the combination of celebrity culture and technology goes a step further. The article presents the phenomenon of virtual celebrities. It focuses on their forms of virtual music idols, which are an intriguing example of technological changes in pop culture. It focuses on projects located in the K-pop market. It aims to present as examples the bands AESPA and SUPERKIND. The article organizes the existing knowledge about virtual idols. Going through the images of such beings in cultural texts and projects of the 1990s, we can now see the emergence of hybrid forms of bands connecting people and digitally created characters. Those broaden the view of the celebrity in today’s world. Following the current technological changes, we can observe the emergence of a fan culture around digital beings. Yet, those practices are not new. However, thanks to technological progress, they are evolving into new forms. In selected examples, the article describes the models and the ways the virtual idols function today. It also poses possible questions related to their future.